"Positioning is, above all, a matter of representation" : J. M. Coetzee and the Transformative Power of Transgression - Stefanova Radoulska, Svetlana (Cultura, Lenguaje y Representación, 2017)
Cultural identity is constructed through and within representation, hence the great interest of postcolonial intellectuals in its creative and ideological potential. In the present essay, I read J. M. Coetzee's novels as innovative sites of transgression that open up an alternative space of interpretation of the literary devices he employs as a source for understanding and illustrating his moral and ethical position. Although he avoids explicit positioning in a binary political thinking and does not publicly establish a relationship between his ideological views and his fiction, the narrative strategies he adopts to represent experiences of suffering and pain speak for themselves. His fiction reveals the author's special interest in the process of creation and interpretation of meaning and in the power of writing. Self-reflexiveness as one of the main features of his texts draws the reader's attention to the linguistic status of representation and suggests that our only access to past events, including historical events, is through discourse.
La identidad cultural se construye mediante y a través de la representación. De ahí el interés de los intelectuales poscoloniales ante su potencial creativo e ideológico. En el presente ensayo, voy a estudiar las novelas de J. M. Coetzee como lugares innovadores de transgresión que, además, despliegan un espacio alternativo de interpretación de los recursos literarios que el autor emplea como fuente para comprender e ilustrar su posición ética y moral. Aunque elautor evita formular su postura en un pensamiento político binario y no establece, públicamente, una relación entre sus posturas ideológicas y sus obras de ficción, las estrategias narrativas que adopta para representar experiencias de dolor y sufrimiento hablan por sí mismas. Sus novelas revelan el especial interés de su autor en el proceso de creación e interpretación del significado así como en el poder de la escritura. La auto-reflexividad, como una de las principales características de sus textos, atrae la atención del lector hacia el estatus lingüístico de la representación y sugiere que nuestro único acceso a eventos del pasado, incluidos los acontecimientos históricos, es a través del discurso.
Keywords: Coetzee; representation; transgression; literary devices; discursive positioning Coetzee; representación; transgresión; estrategias narrativas; posicionamiento discursivo; Emerging; Scopus